Photoaffinity Labeling Study for Identification of the Target Protein of Antimalarial Isoquercitrin - Syamsurizal Syamsurizal; Satoru Tamura; Mohammad Mostaqul Huq; Masafumi Kaneko; Nobutoshi Murakami (Jurnal Matematika & Sains, 2007)
Isoquercitrin (1), a flavonol monoglycoside showed a strong antimalarial activity. In order to identify the target protein in Plasmodium falciparum, a photoreactive isoquercitrin analog, 2-[2-[2-(biotinylaminoethoxy) ethoxy]-4-[3-(trifluoromethyl)-3H-diazirin-3-yl] benzoic acid isoquercitrinyl ester (2) has been synthesized which closely mimics the action of 1. Photoaffinity labeling of 2 revealed the apparent molecular mass of ca 70 kDa on the uninfected erythrocyte membrane.